KULTURA EMOCJONALNA. W POSZUKIWANIU NOWYCH UJĘĆ PRAKTYKI SZKOLNEJ - Góralska, Renata (Rocznik Pedagogiczny, 2018)
The aim of the article is to explain the meaning of the school emotional culture concept. The arti- cle presents following terms: culture, school culture, emotional culture. A few different views on the problem were presented in the text – the views of such sociologists as Erving Goffman, Arlie Hochschild and Steven Gordon. These are the scientists who introduced many new categories to the discussion on the topic of the social contexts of creating and expressing emotions. These are the categories: emotional culture, the feeling rules, emotional ideologies, emotional labour, emotional practice of teaching. By bringing up the issue the author points at the immense heuristic potential of emotional culture and exposes new and interesting fields for the scientists in the educational domain.